Design of wind tunnel (fluid flow analysis) - Koo, Nelton Chwee Yang (2012)
A low speed wind tunnel was design and fabricate. The project covered the process of design and fabrication of the small wind tunnel. In completing this project, a computer aided drawing (CAD) called Solid Work is use to design the wind tunnel. Experiment conducted after build the wind tunnel to find drag coefficient of a sphere. The drag force on a sphere in an air stream was measured at various free stream velocities below 100 m/s. This was done in a low speed wind tunnel using an integral balance system to measure the drag force and a Pitot tube and to measure the velocity. The raw data were processed according to classical equations of fluid mechanics which define the drag coefficient. An impression of fluid field flow around a sphere is also capture using white smoke. Method of analysis the flow in test section was shown by using strings. The experimental results are compared to published results over the range tested.